2010
DOI: 10.1111/j.1365-2834.2010.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of leadership development on emotional health in healthcare managers

Abstract: Transformational leadership practices may influence managers' emotional health. Senior administrative support and communicating the structure and vision of developmental initiatives may help to achieve realistic expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Indeed, both quantitative and qualitative studies published in the field of nursing management have dealt with distress and suffering at work, [2,6] structural factors, [5] factors in employee attraction and retention, [7] emotional health, [9] organizational structure, [14] factors that influence the NM's practice environment, [1,3] and NMs' lack of influence at work. [17][18][19] However, none of these studies have linked these factors to QWL specifically.…”
Section: Overview Of the Scientific Literature On Qwl In The Disciplimentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, both quantitative and qualitative studies published in the field of nursing management have dealt with distress and suffering at work, [2,6] structural factors, [5] factors in employee attraction and retention, [7] emotional health, [9] organizational structure, [14] factors that influence the NM's practice environment, [1,3] and NMs' lack of influence at work. [17][18][19] However, none of these studies have linked these factors to QWL specifically.…”
Section: Overview Of the Scientific Literature On Qwl In The Disciplimentioning
confidence: 99%
“…[1,[4][5][6][7] Shirey et al, [8] Mayrand Leclerc, [1] and Villeneuve [5] have claimed that restructuring of the healthcare system was responsible for the high rate of NMs' absenteeism and turnover. More specifically, several studies [5][6][7][8][9][10][11][12][13][14] have reported that many NMs experienced sluggishness, suffering, and psychological distress in the workplace, which, over the long run, could have negative impacts on their emotional health and QWL. In the past decade, other studies [13][14][15][16][17][18][19] have shown these emergent problems to be accompanied by demoralization, demotivation, and professional burnout.…”
Section: Introductionmentioning
confidence: 99%
“…In managers, social support has been associated with decreased stress and strain [22][23][24], fewer 4 symptoms of burnout [25], higher self-rated health [26], lower physiological stress [27], and less sickness absence [28]. Recent studies have also shown that managers' social support is positively related to other work-related issues besides stress and health, such as leadership development [29][30][31], workplace learning [33], work-life balance [22,34] and performance [35][36]. However, several studies suggest that managers perceive less support in their workplace than non-managers [37][38][39][40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The organizational work space, in terms of arrangement of the physical environment [44], and access to informal arenas for communication [23,[45][46], as well as the degree of control over the job [5], may act as facilitators and influence how people make contact and establish relationships. Organizational practices, such as managers' access to executive education [31,[46][47][48] and mentorship [48][49][50] have also been shown to facilitate the provision of social support to managers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation